The prognostic impact of preoperative mean corpuscular volume in colorectal cancer. (6th March 2022) - Nakamura, Kimihiko; Seishima, Ryo; Matsui, Shimpei; Shigeta, Kohei; Okabayashi, Koji; Kitagawa, Yuko
Abstract: Objective: The relationship between preoperative mean corpuscular volume and postoperative prognosis has been reported in some cancers recently, but no certain consensus has been reached, especially for colorectal cancer. We evaluated the usefulness of mean corpuscular volume as a prognostic factor in colorectal cancer patients. Methods: This study included 1003 patients with colorectal cancer who underwent curative surgery in a single institution. The relationship between mean corpuscular volume values and postoperative recurrence was evaluated by fractional polynomial model. Based on the result, patients were divided into groups according to mean corpuscular volume values. Clinicopathological factors and long-term outcomes were compared between the groups. Results: The risk of postoperative recurrence according to mean corpuscular volume value showed a J-shaped curve, suggesting that both low and high mean corpuscular volume have high risk. Low mean corpuscular volume (≤84 fl) group was oncologically advanced in terms of pathological tumor stage, histological grade and lymphatic invasion with higher inflammation markers. High mean corpuscular volume (>95 fl) group had higher frequency of drinking habit with higher values of aspartate aminotransferase, alanine aminotransferase and γ-glutamyl transpeptidase. Abnormal mean corpuscular volume group including these two groups showed significantly worse disease-free survival than the other ( P < 0.001). Multivariate analysis suggested that abnormal mean corpuscular volume was an independent risk factor for postoperative recurrence (hazard ratio, 1.344; 95% confidence interval, 1.005–1.796; P = 0.046). Furthermore, its prognostic impact was more significant in pStage III than in other stages. Conclusion: Preoperative low and high mean corpuscular volume is a poor prognostic factor in colorectal cancer patients. It could be a predictive marker to estimate worse survival outcome after surgery. Abstract : The usefulness of mean corpuscular volume as a prognostic factor in colorectal cancer patients was evaluated. Both preoperative low and high mean corpuscular volume are high risk of postoperative recurrence.